Language policy in education and its role in preservation of minority languages in Russia and other countries - E.V. Khilkhanova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The language policy in education and the role of education in the preservation and development of minority languages were discussed. The main approaches and models used for teaching minority languages in Russian and Western European schools were compared. Two main approaches were singled out: “old”, when minority languages are poorly represented in education; “new”, which provides an opportunity to learn these languages in schools. The approaches were illustrated by the example of the Frisian and Basque languages, respectively. The problems of teaching minority languages in Russian schools within a broad political context were considered. It was concluded that the positions of minority languages in education are weak due to their little value for careers and social mobility in the current Russian conditions. The possibility and necessity of taking certain educational measures for preservation and development of minority languages in Russia was substantiated. Their complex nature, including both innovations in the education system and the need to overcome the “monolingual ideology”, was emphasized. The recommendations proposed include the use of international experience in organizing civic initiatives and the introduction of new methods and innovative curricula of bilingual education. The most important measures are related to changing the mass consciousness and language culture of society toward identification of Russia as a multinational and multilingual country.